Pengelolaan Program Cerdas Spiritual dalam Pembentukan Akhlakul Karimah di SMA Angkasa Lanud Husein Sastranegara Bandung - Iqbal Arfah Gunawan; Nadri Taja; Ayi Sobarna (Bandung Conference Series: Islamic Education, 2022)
Abstract. The formation of morality is the most important education in addition to science education. In various ways, schools carry out moral formation for students, one of which is SMA Angkasa Lanud Husein Sastranegara Bandung which makes spiritual intelligence programs as a means to form morality. The purpose of this study is to examine the planning, implementation, evaluation and factors that are inhibiting and supporting the spiritual intelligent program to form akhlaq karimah. This study uses a qualitative-descriptive method, namely collecting information about the status of existing symptoms without any engineering. The results of this study indicate that (1) the planning of the spiritual intelligent program includes the background of the formation of the spiritual intelligent program, the objectives of the spiritual intelligent program, indicators of the spiritual intelligent program, the methods used in the spiritual intelligent program and time allocation for the intelligent program. spiritual. (2) The implementation of this spiritual intelligent program is a habit that is carried out every day such as testing the reading of the Qur'an, the habit of reading the Qur'an or Asmaul Husna and continued by praying, habituation of dhuha prayer, habituation of midday prayer in congregation, habituation Friday prayers, the implementation of daughterhood, habituation of infaq and shodaqoh and commemorating major Islamic holidays. (3) Evaluation in forming akhlaq karimah is quite good in its implementation by students, but there are several obstacles and obstacles to achieve it. (4) The inhibiting and supporting factors in this spiritual intelligent program include facilities and infrastructure, student behavior and less than optimal conditioning and support from educators. Abstrak. Pembentukan akhlakul karimah menjadi pendidikan yang paling utama disamping pendidikan ilmu pengetahuan. Dengan berbagai cara sekolah melakukan pembentukan akhlak untuk peserta didik salah satunya SMA Angkasa Lanud Husein Sastranegara Bandung yang menjadikan program cerdas spiritual sebagai sarana untuk membentuk akhlakul karimah. Tujuan dari penelitian ini yaitu untuk mengkaji perencanaan, implementasi, evaluasi dan faktor yang menjadi penghambat serta pendukung dalam program cerdas spiritual untuk membentuk akhlakul karimah. Penelitian ini menggunakan metode kualitatif-deskriptif yaitu mengumpulkan informasi mengenai status gejala yang ada tanpa adanya rekayasa. Hasil dari penelitian ini menunjukkan bahwa (1) perencanaan program cerdas spiritual meliputi latar belakang terbentuknya program cerdas spiritual, tujuan program cerdas spiritual, indikator program cerdas spiritual, metode yang digunakan dalam program cerdas spiritual dan alokasi waktu untuk program cerdas spiritual. (2) Implementasi program cerdas spiritual ini merupakan pembiasaan yang dilakukan setiap harinya seperti pengetesan baca Al-Qur’an, pembiasan membaca Al-Qur’an atau asmaul husna serta dilanjutakn dengan berdo’a, pembiasaan shalat dhuha, pembiasaan shalat dzuhur berjamaah, pembiasaan shalat jum’at, pelaksanaan keputrian, pembiasaan infaq serta shodaqoh dan memperingati hari-hari besar Islam. (3) Evaluasi dalam membentuk akhlakul karimah sudah cukup baik dalam pelaksanaannya oleh peserta didik, namun ada beberapa hambatan serta kendala untuk mencapainya. (4) Faktor yang menjadi penghambat serta pendukung dalam program cerdas spiritual ini meliputi sarana dan prasarana, perilaku peserta didik dan kurang maksimalnya pengondisian dan dukungan dari tenaga pendidik.